Improving engineering process productivity when visualizing waste and mitigating variation - Gerremo, Erik (My University, 2016)
The project is carried out as a case study at FlexLink AB, a global company providing factory conveyor solutions, with head quarter in Gothenburg. Focus has been on the project execution phase called Project Engineering (PE) at four different operating units in Europe. The PE process provides the final project design by using modular designed conveyors; the output of the process is a CAD model and final detailed drawings sent to the assembly workshop where the physical execution takes place. The study investigates the PE process in terms of variation and noise factors. Hence non-value added activities throughout the process were identified by interviews, observations and conduction of a survey. As a backbone throughout the project, the principles of Lean Six Sigma (LSS) has been used. The project aims at identifying critical-to-quality factors of the PE process but also investigating the feasibility of using LSS as a method within project execution at an automation solutions company. An existing gap in documented research has been identified for practical examples of LSS and its applicability in the automation industry. Major findings of the study were an rejection of the existing measurement system and three critical x-factors with remarkable impact on the investigated process and its output. The x-factors were; (i) use of different CAD-tools, (ii) re-drawing and (iii) handover documents – assembly. They all contributed to unwanted non-value-added activities throughout the process. The project enabled possible saving of 1.4 MSEK. In addition, it was concluded that LSS was a feasible method to use for an automation engineering process. Most fruitful was the establishment of a common technical language and enabling of cross-sectional agreements as LSS forces. The thesis work can prove evidence for additional strength of LSS as a method with abilities to reach both organizational and national borders.
Keywords: Produktion; Hållbar utveckling; Industriell organisation, administration och ekonomi; Production; Sustainable Development; Industrial organisation, administration and economics